EFEKTIVITAS CIPORI (CITRUS SPORT DRINK) SEBAGAI MINUMAN UNTUK PENCEGAHAN DEHIDRASI PADA ATLET SEPAK BOLA - Wuri Fitrianingrum; Isti Suryani; Weni Kurdanti (POLTEKKES KEMENKES YOGYAKARTA, 2020)
Football is a high-intensity sport that triggers excess sweat secretions and increases risk of dehydrationhich can reduce athlete’s performance. Regulation of fluid intake is one way to avoid dehydration that can be obtained from natural drinks containing carbohydrates and electrolytes. The study aim to analyzing the effectiveness of the cipori toward the hydration status compared to plain water. This is a Quasi Experimental with pre-post test with control group design. The subjects were 36 teenaage football athletes aged 16-18 years. The treatment group consumed 200ml of cipori and the control group consumed 200ml of plain water every 15 minutes for 30 minutes of running. Hydration status was measured using urine specific gravity. There were significant differences in each group before and after the intervention (p?0,05). The decrease in urine specific gravity before and after the intervention in the control group was 0,59% and in the treatment group was greater at 0,69%. However, no significant differences (p?0,05) were found in the mean difference before and after the intervention of the two groups. Cipori is better than plain water because cipori tends to improve the hydration status of the mean value of urine specific gravity reduction even though there is no significant difference